The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10623-012-9680-8
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Reed–Muller codes revisited

Abstract: We consider weighted Reed-Muller codes over point ensemble S1 × · · · × Sm where Si needs not be of the same size as Sj. For m = 2 we determine optimal weights and analyze in detail what is the impact of the ratio |S1|/|S2| on the minimum distance. In conclusion the weighted Reed-Muller code construction is much better than its reputation. For a class of affine variety codes that contains the weighted Reed-Muller codes we then present two list decoding algorithms. With a small modification one of these algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 27 publications
0
48
0
Order By: Relevance
“…The basic parameters of the projective Reed-Muller-type code C X (d) are equal to those of C X * (d) [22]. A formula for the minimum distance of an affine cartesian code is given in [21, Theorem 3.8] and in [14,Proposition 5]. A short and elegant proof of this formula was given by Carvalho in [5, Proposition 2.3], where he shows that the best way to study the minimum distance of an affine cartesian code is by using the footprint.…”
Section: Applications and Examplesmentioning
confidence: 99%
“…The basic parameters of the projective Reed-Muller-type code C X (d) are equal to those of C X * (d) [22]. A formula for the minimum distance of an affine cartesian code is given in [21, Theorem 3.8] and in [14,Proposition 5]. A short and elegant proof of this formula was given by Carvalho in [5, Proposition 2.3], where he shows that the best way to study the minimum distance of an affine cartesian code is by using the footprint.…”
Section: Applications and Examplesmentioning
confidence: 99%
“…Also in [10] it was observed that the answer to Question 1.1 for the case r = 1 gives the minimum distance of what they called affine cartesian codes. It was brought to our attention by Olav Geil that, these codes were already studied in [7] in a more general setting and the answer to Question 1.1 for r = 1 is a special case of [7,Prop. 5].…”
Section: Introductionmentioning
confidence: 99%
“…An affine Cartesian code of order r is a monomial-Cartesian code C(S, A r ), where A r is as above and S is an arbitrary Cartesian set. This family of codes appeared first time in [20] and then independently in [28]. In [20], the authors study the basic parameters of Cartesian codes, they determine optimal weights for the case when A r is the Cartesian product of two sets, and then present two list decoding algorithms.…”
Section: Introductionmentioning
confidence: 99%